The Effect of Online Learning Using Smansa Ende Online on The Students’ Motivation and Learning Outcomes of Physics Subject of Class XI - Helena V Alung; Melkyanus Bili Umbu Kaleka; Ana Silfiani Rahmawati (Journal of Science Education Research, 2022)
The study aimed to find out the effect of online learning using Smansa Ende online on motivation to learn physics and the effect of online learning using Smansa Ende online on physics learning outcomes, to students in class XI at SMA Negeri 1 Ende for the academic year 2020/2021. Quantitative research was used to examine the causal relationships that were not treated by researchers and the occurred activities. The data collection techniques were questionnaires and documentation. The population was 71 students of class XI MIPA 4 and XI MIPA 5 at SMAN 1 Ende, with a research sample of 36 students of class XI MIPA 5. The hypothesis testing using linear regression t-test showed that H1 and H2 were accepted, with a significance value of H1 being less than 0.05 (0.026 0.050). Then, there was an effect of online learning using Smansa Ende Online on learning motivation. Meanwhile, the significant value of H2 was less than 0.05 (0.007 0.050). Then, there was an effect of online learning using Smansa Ende Online on learning motivation.